PENGARUH PEMBELAJARAN KONTEKSTUAL BERBANTUAN HANDS ON ACTIVITY TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIK DAN RASA INGIN TAHU SISWA - Niken Dwi Listriani; Khafidhoh Nurul Aini (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2019)
The study aims to determine whether there is an influence On mathematical problem-solving skills and the curiosity of students among those following Hands-On Activity Contextual learning and students who follow conventional learning On the opportunity material in class VIII SMPN 1 Karanggeneng. Based on the results of the study using T-test on the ability to solve mathematical problems, then get T_hitung = 5.38 to know the value of T table with the degree of freedom (DK) = 62 with a significance level of 5%, from the results of calculations, at can be valued t _ Table = 1.99. By comparing the T_hitung and T_tabel, then T_hitung > T_tabel (5.38 > 1.99), this means H_0 in the decline and H_1 in the receive, while the attitude of curiosity students can be seen from the calculation by using a test T-Test then obtained T_hitung = 2.57 with T _ ( The degree of Freedom 62 with a significance of 5% equivalent to 1.99. The result of calculating T with a level of significance of 5% is stated significantly that the T_hitung > T (table) > 1, (2.60 > 1.99). This means that H_0 is rejected and H_1 received. It is concluded that Hands-On Activity contextual learning has a significant influence on the ability to solve mathematical problems and students ' curiosity.